Scene of the crime - Brubaker, Ed 1966-; Lark, Michael; Phillips, Sean (Image Comics, Inc., 2012)
"P.I. Jack Herriman has seen too many dead bodies, but that's the family curse, because his uncle is the most famous crime scene photographer since WeeGee. Reeling from a case gone wrong, Jack tackles a missing persons job that should be easy, but instead leads straight into the secrets and lies of a bizarre sex cult"...Page 4 of cover